Efficacy of neem oil sprays and thiamethoxam-metalaxyl cutting dips in the management of cassava whitefly (Bemisia tabaci) - Issa, K.A.; Wosula, E.N.; Amour, M.; Ndalahwa, M.; Bruce, T.; Legg, J.P. (2025)
The cassava whitefly (Bemisia tabaci) is a threat to cassava production as a pest and a vector of viruses that cause devastating cassava mosaic (CMD) and cassava brown streak (CBSD) diseases. The objective of this study was to evaluate the efficacy of neem oil treatments and insecticides against the cassava whitefly. Field plot experiments were conducted to evaluate neem oil products in 2022/2023 and neem oil combined with cutting dipping in a ‘MandiPlus’ formulation (containing Thiamethoxam, Fludioxonil & Metalaxyl-M) in 2023/2024. MandiPlus was applied once as a cutting dip at planting, while neem oil products were sprayed on a monthly basis up to 6 months after planting. The experimental design for field experiments was a randomised complete block design with four replicates. The data recorded for field experiments were on whitefly adult and nymph numbers, CMD and CBSD incidence and severity, and root yield. Neem oil treatments alone reduced whitefly adults and nymphs by 45%–70%, MandiPlus alone gave reductions of 68%–74% and MandiPlus + Neem gave a reduction of 70%. CMD (35%–54%) and CBSD (46%–100%) incidences at 6 months did not differ from control. Root yield increased by 1.8–2.0 kg/plant (78%–87%) in treatments incorporating MandiPlus, while neem oils provided a gain of 0.4–1.9 kg/plant (17%–56%). These findings confirm that the application of MandiPlus through cutting dips is effective at reducing whitefly populations and increasing yield. The application of neem oils alone conferred a significant yield gain in one season but combining with MandiPlus did not confer additive protection and yield gain. Cutting dipping in insecticides is therefore recommended for adoption as a component of integrated pest management for the control of whiteflies and the viruses that they transmit.